Heteroleptic dirhodium (II,II) complexes: synthesis, spectroscopy and applications in hydroformylation and hydroaminomethylation catalytic reactions - de Doncker, Stephen George (Department of Chemistry, 2025)
The synthesis of a series of bis-substituted heteroleptic dirhodium(II,II) complexes containing bridging acetate and chelating bipyridyl ligands is herein described. The protons at the 4- and 4'- positions of the bipyridyl ligands on the model complex 1 were substituted by either the electron withdrawing CF3 (complex 2) or electron donating OMe (complex 3) groups, to observe the electronic influence on the metal complexes. As such, electroanalysis using cyclic voltammetry indicated variations in the metal-centred redox processes for the title complexes. The complexes obtained were used as pre-catalysts for the hydroformylation and hydroaminomethylation of olefins, an unprecedented homogenous catalysis system.